STEP Agri-Competition - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2021)
The initiative is part of efforts to attract, retain and change the perception of secondary school students about agriculture. The competition will also propel students into channelling their aspirations towards embracing careers and businesses in agriculture, acquiring knowledge and developing the right attitude towards agriculture.